2022
DOI: 10.30682/nm2204g
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ opinion about Syrian workers in agricultural sector in Turkey: Case study of Gaziantep

Abstract: Due to the Syrian Civil War, many Syrians have had to flee their country and seek refuge in neighbouring countries, and they face a great deal of financial and social problems in their new countries of residence. Problems such as language barriers and hostility from the host community make it difficult for refugees to integrate into the countries which took them in, and the fact that they must become a part of the work force as a matter of priority to meet their daily needs means that they often work unskilled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…This is due to the rapid urbanization of the region and the large labor shortage in the agricultural field as local farmworkers move to different sectors. Contrary to this result, Cento and Bahşi [32] stated that the main reason for the preference for refugee workers is low wages (78.8%), and some other studies also reported that Syrian migrants generally become laborers for low wages [23,[68][69][70]. The fact that foreign workers work with low wages does not contradict the fact that there is a labor shortage.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This is due to the rapid urbanization of the region and the large labor shortage in the agricultural field as local farmworkers move to different sectors. Contrary to this result, Cento and Bahşi [32] stated that the main reason for the preference for refugee workers is low wages (78.8%), and some other studies also reported that Syrian migrants generally become laborers for low wages [23,[68][69][70]. The fact that foreign workers work with low wages does not contradict the fact that there is a labor shortage.…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, Dedeo glu [7] explained that one reason for lower wages is that wages vary for different groups of workers, and therefore, the productivity-wage relationship is established. Some studies found that the main reason for farmers hiring foreign farmworkers is low wages [31,32]. In addition, some studies focused on the role of immigrants in the labor supply gap in agriculture.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Mulazzani et al (2020), first aimed to outline the link between food security and migration, and then to validate it using the empirical literature from the African continent. Cento and Bahşi (2022) evaluated the situation of Syrian agricultural workers under temporary protection in Turkey from the perspective of farmers.…”
Section: Introductionmentioning
confidence: 99%